2018
DOI: 10.1080/19439342.2018.1452778
|View full text |Cite
|
Sign up to set email alerts
|

Teacher pay and student performance: evidence from the Gambian hardship allowance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
2
17
0
1
Order By: Relevance
“…Yet this tradeoff may not be as stark in secondary schools starting from a low enrollment base, as in this study. Moreover, in recent years the Gambian government has engaged several initiatives toward improving learning outcomes, including promoting decentralized school governance (Blimpo and Evans 2011) and salary premiums for teachers in rural schools Schroeder 2014a, 2014b). The findings from this study suggest that complementary efforts to expand access to schooling, such as the girls' scholarship program, need not impede school quality.…”
mentioning
confidence: 75%
“…Yet this tradeoff may not be as stark in secondary schools starting from a low enrollment base, as in this study. Moreover, in recent years the Gambian government has engaged several initiatives toward improving learning outcomes, including promoting decentralized school governance (Blimpo and Evans 2011) and salary premiums for teachers in rural schools Schroeder 2014a, 2014b). The findings from this study suggest that complementary efforts to expand access to schooling, such as the girls' scholarship program, need not impede school quality.…”
mentioning
confidence: 75%
“…Studies by Glewwe and Kremer () and Harbison and Hanushek () have indicated that quite minor increases in financial incentives linked to improving pupil performance lead to improved learning quality. Pugatch and Schroeder () report that raising monetary incomes leads to test‐score improvements among high‐achieving students. A problem, however, with this kind of strategy is that it requires considerable effort from the administration of government schooling systems to introduce changes in the pay structure.…”
Section: Some Evidence Of Input‐based Approaches To Learning Outcomesmentioning
confidence: 99%
“…There is large body of work studying the effectiveness of pay-for-performance schemes. 5 Relatively fewer studies consider policy effects of unconditional wage increases on teacher turnover (Clotfelter et al, 2008) and student outcomes (de Ree et al, 2018;Pugatch and Schroeder, 2018;Cabrera and Webbink, 2020).…”
Section: Introductionmentioning
confidence: 99%